(untitled) (Applied Biological Research, 2024)
A marked increase in antimicrobial resistance among common bacterial pathogens has made the search for new therapeutic targets highly imperative. The present study was aimed to analyse the potential of bacterial chaperone high-temperature protein G (HtpG) as a therapeutic target by determining its role in virulence and antibiotic resistance. Two bacterial isolates obtained from the oral cavity of healthy human subjects were characterized and tentatively identified as Staphylococcus aureus and Streptococcus mutans. Survival assays of these isolates showed induction of thermotolerance with around 24% increase in survival at lethal temperature after preconditioning. Protein profile studies revealed prominent expression of proteins of 99, 77 and 40 kDa in thermo tolerance group as compared to the control. HtpG inhibition was achieved by using a pharmacological inhibitor of human Hsp90, geldanamycin (GA). In disc diffusion assays, there was no significant inhibitory impact of HtpG on antibiotic susceptibility to six antimicrobial compounds in both the isolates as compared to the control. An 18-19% reduction in biofilm-forming capacity was observed for both isolates after GA treatment. This study lays strong experimental evidence to the involvement of HtpG in the development of anti-microbial resistance through biofilm formation.